Impact of Monetary Policy and its Transmission Mechanism in Sudan - Naeem, Mahmoud Hamid Arabi; Arabi, Khalafalla Ahmed Mohamed; El-Maeia, Howida Adam (Technium Social Sciences Journal, 2023)
The current paper investigates the impact of monetary policy and its transmission mechanism in Sudan, using the structural vector autoregressive (SVAR) model utilizing monthly data from Jan 2000 to the end of 2021. The findings show that Sudan's monetary transmission mechanism for credit and exchange rate channels performs poorly due to the salient features of the Sudanese economy and the financial and banking sector. The policy implication arising from this finding is; the role of the conduct approach for monetary policy should be clearly defined. Moreover, it is necessary to restore the credibility and reliability of the Central Bank of Sudan (CBOS) for conducting monetary policy. Sudan's monetary and credit policies must rely on indirect instruments, and the exchange rate should be determined by the market. The banking sector should be subjected to a program of reform and recapitalization. Other financial institutions, such as insurance companies and pension funds, must play a greater role in the economy.